Realizing People's Welfare in Economic Globalization, Perspective of the Law on Information and Electronic Transactions - Finna Nazran; Fitri Yanni Dewi Siregar (Veteran Law Review, 2022)
Globalization that occurs in the economic field today certainly affects the trade between several countries that are free. This is due to the fact that the use of technology has encouraged rapid business growth, because various information can be presented through long distance relationships and those who wish to conduct transactions do not have to meet face to face, but simply through computer and telecommunications equipment. Utilization of ITE Technology is carried out based on the principles of legal certainty, benefits, prudence, good faith, and freedom to choose technology or technology neutrality. This study aims to determine the development and concept of people's prosperity in economic globalization in Indonesia, with the presence of the ITE Law in creating a just economy. This research uses normative legal research which is descriptive analytical with a qualitative approach to primary data, secondary data and tertiary data which includes the content and structure of positive law. used as a reference in reviewing legal issues that are the object of study. The results of the study indicate that the existence of the ITE Law in creating a just economy at this time has major implications for the development of social life . Economic justice must be understood as a condition where the people control the course of economic activity, through the use of information and technology which is carried out based on the principles of legal certainty, benefits, prudence, good faith, and freedom to choose technology or technology neutrality. This is in line with the goals of the state as stated in the fourth paragraph of the Preamble to the 1945 Constitution.